ATP7B-Deficient Hepatocytes Reveal the Importance of Protein Misfolding Induced at Low Copper Concentration - Charbonnier, Peggy; Chovelon, Benoît; Ravelet, Corinne; Ngo, Tuan Dung; Chevallet, Mireille; Deniaud, Aurélien (Cells (Basel, Switzerland), 2022)
Copper is a transition metal essential for human life. Its homeostasis is regulated in the liver, which delivers copper to the whole body and excretes its excess outside the organism in the feces through the bile. These functions are regulated within hepatocytes, and the ATP7B copper transporter is central to making the switch between copper use and excretion. In Wilson disease, the gene coding for ATP7B is mutated, leading to copper overload, firstly, in the liver and the brain. To better understand the role of ATP7B in hepatocytes and to provide a smart tool for the development of novel therapies against Wilson disease, we used the CrispR/Cas9 tool to generate hepatocyte cell lines with the abolished expression of ATP7B. These cell lines revealed that ATP7B plays a major role at low copper concentrations starting in the micromolar range. Moreover, metal stress markers are induced at lower copper concentrations compared to parental cells, while redox stress remains not activated. As shown recently, the main drawback induced by copper exposure is protein unfolding that is drastically exacerbated in ATP7B-deficient cells. Our data enabled us to propose that the zinc finger domain of DNAJ-A1 would serve as a sensor of Cu stress. Therefore, these Wilson-like hepatocytes are of high interest to explore in more detail the role of ATP7B.